2016
DOI: 10.1007/s10162-016-0586-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Regularity Detection and Rate Discrimination in Cochlear-Implant Listeners

Abstract: Cochlear implants (CIs) convey fundamental-frequency information using primarily temporal cues. However, temporal pitch perception in CI users is weak and, when measured using rate discrimination tasks, deteriorates markedly as the rate increases beyond 300 pulses-per-second. Rate pitch may be weak because the electrical stimulation of the surviving neural population of the implant recipient may not allow accurate coding of inter-pulse time intervals. If so, this phenomenon should prevent listeners from detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Overall performance was generally better for Slow rates than Fast rates or Ultra-Fast rates for CI users. This is consistent with previous studies reporting a decrease in performance with increasing rate in various temporal tasks with CI listeners, such as rate discrimination or temporal jitter detection (Gaudrain, Deeks, & Carlyon, 2017;Macherey, Deeks, & Carlyon, 2011;Vandali & van Hoesel, 2012). Thus, it is likely that our observation of a decrease in overall performance with rate can be accounted for by mechanisms independent of the learning process.…”
Section: B Effect Of Ratesupporting
confidence: 93%
“…Overall performance was generally better for Slow rates than Fast rates or Ultra-Fast rates for CI users. This is consistent with previous studies reporting a decrease in performance with increasing rate in various temporal tasks with CI listeners, such as rate discrimination or temporal jitter detection (Gaudrain, Deeks, & Carlyon, 2017;Macherey, Deeks, & Carlyon, 2011;Vandali & van Hoesel, 2012). Thus, it is likely that our observation of a decrease in overall performance with rate can be accounted for by mechanisms independent of the learning process.…”
Section: B Effect Of Ratesupporting
confidence: 93%
“…While there is no way to absolutely rule out the possibility that individual differences in cognitive function, for example, due to aging, may have contributed to our pattern of results, it can be argued that this is rather unlikely. Indeed, 3AFC tasks similar to the one used in the present study have been used in other studies where performance of the CI group was found to be equivalent or better than that of the NH group (gap detection in words: Gaudrain et al, Reference Note 2 ; rate pitch discrimination: Gaudrain et al 2017 ). As for age, the NH listeners were on average 22.7 years younger than the CI listeners.…”
Section: Discussionmentioning
confidence: 85%
“…The perception of temporal pitch is based on the periodicity of the signal or of the temporal envelope of the signal. Temporal pitch perception seems to be relatively preserved in CI listeners, and they demonstrate functional use of this pitch cue similar to that of NH listeners ( Hong & Turner 2009 ; Deroche et al 2014 ; Gaudrain et al 2017 ), as long as F0 remains below 300 Hz ( Shannon 1983 ; Carlyon et al 2002 , 2010 ; Zeng 2002 ). In contrast, place pitch, that is, the pitch that results from exciting different segments of the cochlea, seems to be more difficult to use for CI listeners ( Geurts & Wouters 2001 ; Laneau et al 2004 ), in particular in speech-like stimuli where dynamic spectral envelope fluctuations may interfere with spectral changes induced by F0 differences ( Green et al 2002 , 2004 ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Pitch information coded via place of excitation, i.e., differential excitation of the auditory nerve fibers of different characteristic frequencies, is limited (Moore, 2003). CI listeners rely also on temporal processing of the repetition rate of electrical pulses to perceive pitch (Bahmer and Baumann, 2013; Baumann and Nobbe, 2004; Carlyon et al, 2010; Venter and Hanekom, 2014; Gaudrain et al, 2017). Previous studies show that CI listeners are able to identify musical intervals and even recognize melodies by varying the rate of stimulation delivered on a single electrode (Pijl and Schwarz, 1995; McDermott and McKay, 1997).…”
Section: Introductionmentioning
confidence: 99%